An Overview of Health Issue Tracking among Parents of School-Aged Children - Permana, Lies; Ifroh, Riza Hayati (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2022)
School age is one of the community groups that is a priority for the national health program. Various health problems of school-age children are a concern of parents. To deal with their school age children's condition, parents require a variety of health issues solutions. Parents commonly prefer to seek for information on their gadgets by using the internet. These many concerns, problems, and issues that parents have about their children's health have motivated an in-depth exploration of parents' digital literacy skills in tracing information. This study aims to determine the frequency with which parents of school-aged children track health information and investigate the issue that 109 parents of school-aged children are interested in based on health issues in East Kalimantan. The sample was chosen using an accidental sampling technique. In this study, a simple questionnaire with closed and open questions was used as a survey method. A univariate and bivariate test were performed to process data on frequency with which parents seek health problems as well as its relationship to respondent characteristics, the Spearman rank test was used. The result is health information about screen time risk was most frequently accessed by parents, but compared to other issues, the nutrition issue is significantly deeper. It will be necessary to develop interventions like health promotion programs that parents will utilize in improving their health literacy, especially about children’s health in the school